Afterword: Comparison in the Anthropological Study of Plural Religious Environments. Issue 1 (1st March 2020) - Meyer, Birgit
Abstract: Highlighting common threads in the pieces by Beekers, Kasmani and Mattes, and Dilger, this concluding essay reflects on the potential of comparison as conceptual innovation in the anthropological study of religious plurality. Asking how to develop innovative practices of comparison for the sake of grasping the dynamics of plural societies in the light of the articles in this collection, I argue that it is necessary to transcend the bifurcation of the study of religions, which was accentuated with the rise of the anthropologies of Islam and Christianity, in favor of a focus on the secular configuration as a whole, paying attention to power dynamics that assign different spaces for action to different religions (notwithstanding their equality in legal terms). The point of comparison, understood as a critical project geared toward conceptual innovation, is not only to discern so far overlooked, unexpected differences and similarities, but also to understand how these differences and similarities, as well as the possibility to compare as such, are outcomes of long-standing entanglements.